Clinical and Prognostic Significance of Coagulation Assays in Advanced Epithelial Ovarian Cancer. Issue 2 (1st February 2013) - Tas, Faruk; Kilic, Leyla; Bilgin, Elif; Keskin, Serkan; Sen, Fatma; Ciftci, Rumeysa; Yildiz, Ibrahim; Yasasever, Vildan
Abstract : Objective: Epithelial ovarian cancer (EOC) is the leading cause of death among gynecological tumors and usually diagnosed at advanced stage. We aimed to identify the clinical and prognostic relevance of coagulation tests and their correlation with serum CA-125 levels in advanced EOC. Materials and Methods: A total of 33 advanced-stage (stages III and IV) EOC patients were enrolled in the study. Of these patients, 17 had received neoadjuvant chemotherapy and 16 patients received chemotherapy after optimal debulking surgery. Several clinicopathologic factors, coagulation assays, routine biochemistry tests, and serum CA-125 levels were evaluated before treatment and compared with healthy subjects. Results: All coagulation tests including prothrombin time (PT), activated partial thromboplastin time, international normalized ratio, fibrinogen, D-dimer, and platelet revealed statistically significant difference between patients and control subjects ( P ⩽ 0.001). Elevated CA-125 levels were correlated with higher D-dimer values ( P = 0.03). Prolonged PT was associated with poorer both overall ( P = 0.03) and progression-free survival rates ( P = 0.04). Conclusions: Correlation of CA-125 with D-dimer is supposed to reflect hyperactivation of fibrinolytic pathway in the presence of a higher tumor load. Alterations in coagulation pathway reflected by prolonged PT support prognostic effects on survival of advanced-stage EOC patients.